1995
DOI: 10.1016/s0960-9822(95)00279-x
|View full text |Cite
|
Sign up to set email alerts
|

Physical interaction between a novel domain of the receptor Notch and the transcription factor RBP-Jκ/Su(H)

Abstract: We show that the transcription factor RBP-J kappa/Su(H) interacts directly with a novel intracellular domain of the cell-surface receptor Notch. RBP-J kappa/Su(H) does not appear to interact with Notch via the CDC10/ankyrin repeats implicated in previous studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
362
1
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 440 publications
(370 citation statements)
references
References 43 publications
6
362
1
1
Order By: Relevance
“…Our results demonstrated that Notch1-IC transcriptional activity was inhibited by the presence of Dll1-IC, which suggests that Dll1-IC may also involve the suppression of Notch1-IC transcriptional activity. In previous reports, it has been determined that Notch1-IC and RBP-Jk are the key components in the Notch1-IC transcription complex (Tamura et al, 1995). Then Notch1-IC recruits coactivator, Mastermind like-protein MAML.…”
Section: Discussionmentioning
confidence: 99%
“…Our results demonstrated that Notch1-IC transcriptional activity was inhibited by the presence of Dll1-IC, which suggests that Dll1-IC may also involve the suppression of Notch1-IC transcriptional activity. In previous reports, it has been determined that Notch1-IC and RBP-Jk are the key components in the Notch1-IC transcription complex (Tamura et al, 1995). Then Notch1-IC recruits coactivator, Mastermind like-protein MAML.…”
Section: Discussionmentioning
confidence: 99%
“…The best-described intracellular domain of Notch1 contains five different segments: i) seven tandem-ankyrin repeats, ii) the transactivation domain, iii) a glutamine-rich OPA domain, iv) a proline-, glutamine-, serine-and threonine-rich PEST domain and v) a RAM23 domain [93 -95]. The RAM23 domain contains the nuclear localization signals (NLSs) and is in combination with the ankyrin-repeats responsible for the binding to RBP-J [94,96]. The region between the ankyrin-repeats and the PEST region is the transactivation domain (TAD) of NICD, [97].…”
Section: Coactivators Of Notchmentioning
confidence: 99%
“…Previous biochemical and cellular studies demonstrated that both NICD and corepressors interact primarily with CSL through a central region corresponding to the beta-trefoil domain, reviewed in [104]. NICD primarily interacts strongly through its RAM-domain, but only weakly through its ankyrin repeats [94]. However, the ankyrin repeats are needed for the formation of the RBP-J/NICD/MAML ternary complex and transcriptional activation [10].…”
Section: Structure Of the Rbp-j/nicd/maml Coactivator Complexmentioning
confidence: 99%
“…The NICD mainly contains membrane‐proximal RAM domain, an ANK domain, and C‐terminal PEST motif 3 . The NICD migrates to the nucleus and associates at high affinity with DNA‐binding factor CSL through the RAM domain 20. Meanwhile, the ANK domain weakly interacts with both CSL and a shorter sequence at the N‐terminal end of mastermind‐like 1 (MAML1) protein (the transcriptional co‐activator)21, 22.…”
Section: Notch Signalingmentioning
confidence: 99%